Effects of Digital Intervention on Improving Self-Management Patients with Peritoneal Dialysis: A Systematic Review - Cahyaningsih Efendi; Ninuk Dian Kurniawati; Herdina Mariyanti (Indonesian Journal of Global Health Research, 2024)
Continuous Ambulatory Peritoneal Dialysis (CAPD) is an effective alternative for renal failure patients to undergo treatment with more independence and flexibility. However, the success of CAPD is highly dependent on the patient's skills and knowledge. Many patients lack sufficient information, which may hinder the effectiveness of the dialysis process. The Objectives of this study is to determine the best way to use digital interventions to enhance self-management capabilities in peritoneal dialysis patients. A systematic review following the PRISMA 2020 guidelines was conducted. Article selection used PICO. The research focused on peritoneal dialysis patients and how the use of applications to improve self-management skills. article searches in 2015-2024 in 4 databases, namely EBSCO, Proquest, Scopus, and Pubmed databases. MeSH was used in the medical domain for keyword search. Papers were evaluated for quality using the Jonna Briggs Institute (JBI) framework. There were 7 relevant papers found in the literature search. Implementing digital interventions in healthcare in peritoneal dialysis patients has been used worldwide. Digital interventions used include the use of mobile health text messages, websites and apps. Significant improvements in peritoneal dialysis-related knowledge as well as patient satisfaction are characteristic of most therapies. The resulting impact of digital interventions varies widely with the attitudes and decision-making of individuals undergoing peritoneal dialysis. Digital interventions present a new approach to enhancing self-management capabilities in patients with chronic kidney disease who use peritoneal dialysis. The use of technology can provide the necessary support to manage their condition effectively.